The Effect of Bilingual Exposure on Executive Function Skills in Preterm and Full-Term Preschoolers. Issue 7 (September 2016) - Loe, Irene M.; Feldman, Heidi M.
ABSTRACT: Objective: To evaluate the effects of bilingual exposure on executive function (EF) skills, measured by parent-rating and performance-based instruments, in preterm and full-term preschoolers. Method: Children age 3 to 5 years (mean 4.4) born preterm (PT; n = 82) and full term (FT; n = 79) had monolingual (PT-M, n = 51; FT-M, n = 53) or bilingual (PT-B, n = 31; FT-B, n = 26) language exposure. Groups were similar in age, gender and race, but PT children had lower socioeconomic status (SES) than FT children. Parents completed a language questionnaire and diary and a standardized parent rating of EF skills. Children completed EF tasks that tap response inhibition, working memory, and cognitive flexibility. ANCOVA and logistic regression examined effects on EF of birth group (PT/FT), language status (M/B), and birth group by language status interaction, controlling for age and SES. Results: Compared to children born FT, children born PT had significantly higher parent-rated EF scores and poorer performance on all but one EF task, both indicating more EF problems. No main effects of language status and no birth group by language status interactions were significant. Conclusion: PT status was clearly associated with poorer EF skills, similar to many other studies. In this sample, bilingual exposure conferred neither an advantage nor disadvantage in the FT and PT group. This information may prove useful in counseling families of both PT and FT children about the impact of bilingual exposure on their children's cognitive skills.